Clinical Features of Human Metapneumovirus-Associated Community-acquired Pneumonia Hospitalizations. (3rd February 2020) - Howard, Leigh M; Edwards, Kathryn M; Zhu, Yuwei; Grijalva, Carlos G; Self, Wesley H; Jain, Seema; Ampofo, Krow; Pavia, Andrew T; Arnold, Sandra R; McCullers, Jonathan A; Anderson, Evan J; Wunderink, Richard G; et al.
Abstract: Background: Human metapneumovirus (HMPV) is a leading cause of respiratory tract infections. Few studies have compared the clinical characteristics and severity of HMPV-associated pneumonia with other pathogens. Methods: Active, population-based surveillance was previously conducted for radiographically confirmed, community-acquired pneumonia hospitalizations among children and adults in 8 United States hospitals. Clinical data and specimens for pathogen detection were systematically collected. We described clinical features of all HMPV-associated pneumonia and, after excluding codetections with other pathogen types, we compared features of HMPV-associated pneumonia with other viral, atypical, and bacterial pneumonia and modeled the severity (mild, moderate, and severe) and length of stay using multivariable proportional odds regression. Results: HMPV was detected in 298/2358 (12.6%) children and 88/2320 (3.8%) adults hospitalized with pneumonia and was commonly codetected with other pathogens (125/298 [42%] children and 21/88 [24%] adults). Fever and cough were the most common presenting symptoms of HMPV-associated pneumonia and were also common symptoms of other pathogens. After excluding codetections in children (n = 1778), compared to HMPV (reference), bacterial pneumonia exhibited increased severity (odds ratio [OR], 3.66; 95% confidence interval [CI], 1.43–9.40), respiratory syncytial virus (RSV; OR, 0.76; 95% CI, .59–.99) and atypical (OR, 0.39; 95% CI, .19–.81) infections exhibited decreased severity, and other viral pneumonia exhibited similar severity (OR, 0.88; 95% CI, .55–1.39). In adults (n = 2145), bacterial (OR, 3.74; 95% CI, 1.87–7.47) and RSV pneumonia (OR, 1.82; 95% CI, 1.32–2.50) were more severe than HMPV (reference), but all other pathogens had similar severity. Conclusions: Clinical features did not reliably distinguish HMPV-associated pneumonia from other pathogens. HMPV-associated pneumonia was less severe than bacterial and adult RSV pneumonia, but was otherwise as or more severe than other common pathogens. Abstract : Clinical features did not reliably distinguish human metapneumovirus (HMPV) pneumonia from other pathogens. HMPV pneumonia was less severe than bacterial and adult respiratory syncytial virus pneumonia but was similar or more severe than other viral and atypical pathogens.